FRACTURE RESISTANCE OF SIMULATED IMMATURE PERMANENT TEETH WITH ANATOMIC POST - Chareonwutilap, Krittika; Wimonchit, Suwit; Sakdee, Jaruma (Srinakharinwirot University Journal of Sciences and Technology, 2023)
Objective: To compare the fracture resistance of simulated human immature teeth that had ProRoot® MTA as apical barriers and then restored with an anatomic post and filled in the entire root canal with ProRoot® MTA, then restored with composite resin. Materials and methods: Thirty extracted human mandibular premolars were prepared to be artificial immature teeth. They were randomly divided into three groups, 10 teeth each by the stratification size of the tooth. Group I – no root canal filling, Group II - 3 millimeters apical plug of ProRoot® MTA and anatomic post and Group III – entire root canal filled with ProRoot® MTA and composite restoration. The sample was subjected to static compression loads, 30 degrees to their long axis, until fractured under a Universal Testing Machine. The maximum force to fracture was recorded in Newtons and analyzed by One-Way ANOVA and Tukey’s Honestly Significance Difference (HSD). Results: From the statistical analysis, the mean load to fracture was found to be different at a statistically significant level among the groups. Following the Post-hoc test showed that the load in Group I (721.43 ± 95.80 newtons) were statistically lower than Group II (1,115.01 ± 101.50 newtons) and Group III (1,071.04 ± 124.97 newtons). One-third of the cervical were shown in the major fracture point which were presented in an oblique fashion from crown through root direction. Conclusions: Reinforcement of immature teeth with anatomic post or entire root canal filling with ProRoot® MTA effectively increased fracture resistance with no differences. The common fracture level was found at the crown and one-third cervical of the root levels.